2021
DOI: 10.1097/cce.0000000000000508
|View full text |Cite
|
Sign up to set email alerts
|

Legionella Pneumonia in the ICU: A Tertiary Care Center Experience Over 10 Years

Abstract: Few studies have reported the complications and outcomes of patients with Legionella pneumonia requiring ICU admission. The objective of our study is to report the clinical course, complications, and 30-day mortality of patients with Legionella pneumonia admitted to the critical care units at our medical center over a 10-year period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 33 publications
2
16
1
1
Order By: Relevance
“…5 The mortality rate in patients with Legionella pneumonia who are admitted to an intensive care unit is between 9.1% and 41.7%. [6][7][8] Furthermore, there are certain patient populations (those with immunosuppression, chronic lung disease, history of smoking, or age over 50) that are more susceptible to severe CAP from Legionella. 4 For example, Legionella pneumonia patients with cancer can have a case-fatality rate as high as 31%.…”
Section: ■ Clinical Characteristics Of Legionella Pneumoniamentioning
confidence: 99%
“…5 The mortality rate in patients with Legionella pneumonia who are admitted to an intensive care unit is between 9.1% and 41.7%. [6][7][8] Furthermore, there are certain patient populations (those with immunosuppression, chronic lung disease, history of smoking, or age over 50) that are more susceptible to severe CAP from Legionella. 4 For example, Legionella pneumonia patients with cancer can have a case-fatality rate as high as 31%.…”
Section: ■ Clinical Characteristics Of Legionella Pneumoniamentioning
confidence: 99%
“…Morbidity and mortality in Legionnaires' disease remains high. Intensive care unit (ICU) admission rates reported in studies range from 20 to 27% [ 1 , 7 , 14 16 ]. Andrea et al [ 14 ] also found elevated frequency of invasive mechanical ventilation, septic shock, acute respiratory distress syndrome, and acute kidney injury among those patients requiring ICU admission.…”
Section: The Scale Of the Problemmentioning
confidence: 99%
“…Intensive care unit (ICU) admission rates reported in studies range from 20 to 27% [ 1 , 7 , 14 16 ]. Andrea et al [ 14 ] also found elevated frequency of invasive mechanical ventilation, septic shock, acute respiratory distress syndrome, and acute kidney injury among those patients requiring ICU admission. Moreover, Legionnaires' disease has an overall mortality rate of 4–18% [ 7 , 14 18 ].…”
Section: The Scale Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…In severe cases, patients may develop acute respiratory distress syndrome (ARDS) requiring intensive care unit (ICU) admission. Rates of invasive mechanical ventilation (IMV) and mortality is high in patients admitted to the ICU, ranging from 54.5-82.3% and 9.1-41.7% respectively (3)(4)(5). Acute kidney injury (AKI), multiorgan failure and shock are frequently seen and failure to initiate Legionella-speci c antibiotic therapy is associated with worse outcomes (3).…”
mentioning
confidence: 99%